Exogenous Fecal Microbial Transplantation Alters Fearfulness, Intestinal Morphology, and Gut Microbiota in Broilers - Yan, Chao; Xiao, Jinlong; Li, Zhiwei; Liu, Hao; Zhao, Xinjie; Liu, Jian; Chen, Siyu; Zhao, Xingbo (Frontiers in Veterinary Science, 2021)
Fecal microbiota transplantation (FMT) has been documented transplanting a donor fecal sample to a receipt individual for a desired physiologic effect. However, whether the gut microbiota construction, intestinal maturation, and physiological plasticity are modulated by FMT during early life of broilers is not yet known. To evaluate the role of FMT, ninety-six birds were averagely divided into a check (CK) group and a broiler recipient (BR) group, and then production performance, behavior, intestinal development and gut microbiota were determined. Results showed that the fearfulness in the CK group was higher than the BR group in both the behavioral tests (P < 0.05). The muscularis mucosa, muscle thickness and serous membrane thickness in BR group were higher compared to the CK group (P < 0.05). In the gut microbiota, Shannon diversity showed no difference, while beta diversity was presented a difference in principal coordination analysis (PCoA) analysis between the CK and BR groups. At the genus level, Megamonas in the CK group was higher than the BR (P = 0.06) group, respectively. In the BR group, glutamatergic synapse and N-glycan biosynthesis were enriched. Some characteristics of gut microbiota in the donor chickens could be transferred to recipient chickens by FMT. In conclusion, exogenous FMT as a probiotics-like administration might be an efficient way to improve chickens’ physiology and behavior.